Toward an Enactive Conception of Productive Practices: Beyond Material Agency - Di Paolo, Ezequiel (2023)
We examine the question of material agency as raised in material engagement theory (MET). Insofar as MET tends to highlight the causal roles played by extra-bodily material flows in human practices, the term “material agency” does not sufficiently distinguish cases in which these flows are part of an agentive engagement from cases in which they are not. We propose an operational criterion to effect such a distinction. We claim this criterion is organizational, i.e., systemic, and not causal. In the enactive account, agency requires three organizational conditions: self-individuation, interactional asymmetry, and normativity. These conditions can have organic, sensorimotor, and sociomaterial realizations. The dance of human productive practices is indeed spread between brains, bodies, and the world, as MET claims, but it is distributed in an organized manner that involves constraints and norms at various scales. We put forward a relational and non-anthropocentric perspective toward an enactive approach to productive practices. We discuss some aspects of agentive ensembles rendered more intelligible by our proposal, including incorporation, soft assembly and non-decomposability, and the grounding of teleology normative processes at multiple scales. In this manner, we seek to continue the dialog between MET and enactive theory, beginning with the view that a situated system must realize certain minimal organizational conditions to be called an agent.